Special Issues in Responsible Tourism Vol. 2 - Tunkkari-Eskelinen, Minna; Törn-Laapio, Anne; fi=Jyväskylän ammattikorkeakoulu|sv=Jyväskylän ammattikorkeakoulu|en=JAMK University of Applied Sciences| (Jyväskylän ammattikorkeakoulu, 2022)
Promotion of responsible tourism is gained more attention after the intensive periods of COVID-19 restrictions around the world. Tourism is one of the sectors hit hardest by the COVID-19 pandemic, and businesses are lacking work force everywhere in the world. However, the destinations now understand what it is without any tourists around. In some part of the world it is a relief, and in some countries it is miserable situation without any economic impact. The new steps in multidisciplinary research have appeared, and research field is considered more important now than ever before. However, it is still required proactive planning and cooperation between different actors –like in several years ago. What is the future of tourism? It is a question mark for Russian markets during the war operations, but the climate of uncertainty continues all over Europe. The publication is split into three themes following mainly the content of the research papers presented in the 15th International Conference on Responsible Tourism (ICRT 2022) in Oodi Library, Helsinki. Part 1 deals with research work linked to climate change. Examples of ecological perspectives in tourism open the discussion of responsibilities in this publication. Part 2 introduces actions planned and taken towards responsible tourism in the region of Jamk University of Applied Sciences and Central Finland. Visit Jyväskylä Region is the organization taking a destination manager’s role in the beginning of the year 2022 and getting together responsible actions of the companies as well as other communities. The main goal in Central Finland is to reach STF (Sustainable Travelling Finland) label of responsible tourism destination, which in turn is controlled by Visit Finland (Business Finland) operations. Part 3 gives a brief overview of the cases in Finnish Lapland and Iceland. Responsible tourism is already under command of some actors or at least the need for management of responsible tourism becomes an issue. In Finland, we need role models – actors whom to ...